(untitled) (AYUSHDHARA, 2025)
Arsha (haemorrhoids) is commonest anorectal disorder affecting a large portion of the population and is characterized by engorgement and prolapse of superior haemorrhoidal venous plexus. In Ayurveda, Arsha has been classified as a Tridoshaja Vyadhi and Acharya Sushruta has placed it among Ashta Mahagada in Sushruta Samhita. In modern science various treatments are used e.g. conservative measures, non-operative procedures and operative procedures. Acharya Sushruta, Father of surgery, was first to describe Kshara in Sushruta Samhita in an elaborated manner. He has described Bhesaja, Kshara, Agni and Shashtra Karma for treatment of Arsha. Among the various treatments described Pratisaraneeya Kshara Karma (alkaline cauterization) is considered as highly effective and minimally invasive para-surgical procedure for the treatment of haemorrhoids. It offers an alternative way to conventional surgery with lesser complications and minimal chance of recurrence. This research article explains and review about Pratisaraneeya Kshara usage in the treatment of Arsha given by Acharya Sushruta.